Begunska kriza in meja EU - Svetlič, Rok (Teorija in praksa, 2016)
In this article, the phenomenon of the border between the EU and states along the Mediterranean Sea is discussed. The refugee crisis has started the process of transforming the abstract-formal border into a concrete-political one. These borders were drawn by western powers and have therefore never existed in the form demanded by the ontology of the border, i.e. as the relation of absolute otherness. On the contrary, moral and political imperialism was present (substituting the military one) and breaching the border continues to be an easy act. The escalation of the refugee crisis has forced the EU to change the discourse to confront with it. The rhetoric of human rights as a universal concept has been replaced by a particular concept of interest. With this shift, the EU's concrete-political borders along the Mediterranean Sea are constituted which, despite the formal abandonment of the colonial tradition, were never recognised. The result will not be the closing up of the EU; on the contrary, the conditions for the formation of solid relationships between the states of North Africa and the Middle East will emerge. Only the full recognition of subjectivity to these states can contribute to solving the refugee crisis at its origin.
Keywords: begunska kriza; border; European Union; Evropska unija; meje; moral imperialism; moralni imperializem; refugee crisis; Schmitt, Carl, 1888-1985